Tax Avoidance in Review by Institutional Ownership, Firm Size, and Leverage With Profitability as a Moderation Variable (Empirical Research on Manufacturing Companies in Indonesia) - Octaviantary, Astrid Regina; Damayanti, Fera (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This research aims to determine the effect of institutional ownership, firm size, and leverage on tax avoidance with profitability as a moderating variable. The population in this research are manufacturing sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling method used was purposive sampling, so that 158 samples were taken according to the criteria. Data analysis method used is multiple regression analysis absolute difference method. The results of this research indicate that institutional ownership and leverage have an effect on tax avoidance, while firm size has no effect on tax avoidance. Then profitability can strengthen the influence of institutional ownership and leverage on tax avoidance, but profitability cannot moderate the effect of firm size on tax avoidance. The implication of this research is that it can be especially useful for the government so that the government can take preventive measures so that companies do not carry out tax avoidance.